KEEFEKTIFAN VAKSIN Aeromonas hydrophila UNTUK MENGENDALIKAN PENYAKIT MAS(MOTILE AEROMONAS SEPTICEMIA) PADA GURAMI (Osphronemus gouramy Lac.) EFFICACY OF Aeromonas hydrophila VACCINE TO CONTROL MOTILE AEROMONAS SEPTICEMIA (MAS) DISEASE ON GOURAMY (Osphronemus gouramy Lac.) - Mulia, Dini Siswani (Pembangunan Pedesaan, 2007)
The study was aimed to find an antigen (Ag) O and Ag H of Aeromonas hydrophila vaccines as immunogenic antigen and to evaluate the efficacy of these vaccines to control Motile Aeromonas Septicemia (MAS) disease on gouramy. The research was carried out by Completely Randomized Design with three treatments and five replicates, i.e., Ag O of A. hydrophila vaccine, Ag H of A. hydrophila vaccine, and control. Ten gouramy fishes with length of 10-12 cm and average 8 weight of 28 g were used. Soaking method was used with dosage of 10 for 90 minutes. Booster was conducted a week after vaccination and challenging test was conducted a weeks after booster. Parameters observed were antibody titer, Relative Percent Survival (RPS), survival rate, mean time to death (MTD), and water quality. Data were analyzed by Analysis of Variance followed by Duncanâs Multiple Range Test (DMRT). The results showed that Ag O and Ag H of A. hydrophila vaccines could increase antibody titer, survival rate, and RPS (P